Improved emotion regulation following a trauma-informed CBT-based intervention associates with reduced risk for recidivism in justice-involved emerging adults - Dumornay, Nathalie M.; Finegold, Katherine E.; Chablani, Anisha; Elkins, Lili; Krouch, Sotun; Baldwin, Molly; Youn, Soo Jeong; Marques, Luana; Ressler, Kerry J.; Moreland-Capuia, Alisha (Frontiers in Psychiatry, 2022)
Objective: Male youth involved in the juvenile legal system have disproportionate rates of trauma and violence exposure. Many justice-involved youth have untreated mental illness, with an estimated 66% of young men who are incarcerated meeting criteria for at least one mental health disorder, including posttraumatic stress disorder (PTSD), depression, and substance abuse. While Cognitive Behavioral Therapy (CBT) approaches are considered the most effective evidence-based treatments for addressing and treating behavioral and emotional difficulties, male youth with a history of incarceration and youth who are at risk for (re)incarceration, violence, emotion dysregulation, and trauma face significant barriers in accessing these services. Methods: Roca, Inc., an internationally recognized organization moving the needle on urban violence by working relentlessly with young people at the center of violence, employs a trauma-informed CBT-based skills curriculum and approach in their intervention model, to improve youths’ educational, employment, parenting, and life skills opportunities, while decreasing risk for recidivism, addressing trauma and increasing skills for emotion regulation. The aim of this analysis was to assess the effectiveness of Roca’s trauma-informed CBT skills curriculum on youths’ emotional and behavioral outcomes. We analyzed data from over 300 participating emerging adult men from four sites in Massachusetts and one site in Baltimore, Maryland who had at least 3 series of data collection across multiple skills-based sessions. Results: We found improvements in outcomes in overall mean scores related to decreased distress about employment and education, as are expected with standard intervention approaches for justice-involved youth. Participants who show improvement in emotion regulation across engagement (approximately half the cohort), were found to have significant improvements in distress related to relationship and family functioning and self-care, and decreased substance use, along with other outcomes compared to those participants with less improvement in emotion regulation. Furthermore, improvement in different aspects of emotion regulation were associated with improved relationships, life distress, substance use, and improved prosocial thinking. Conclusions: Together, these data suggest that adding mental health support and skills training, such as with trauma-informed CBT models, to programs for justice-involved youth may lead to significant improvements in functioning, quality of life, and mental health outcomes.